Growing farms and groundwater depletion in the Kansas High Plains - Ao, Yufei Z; Hendricks, Nathan P.; Marston, Landon T. (My University, 2021)
The average farm size has more than doubled within the United States over the last three decades, transforming the agricultural industry and rural farming communities. It is unclear, however, how this ubiquitous trend has affected and is affected by the environment, particularly groundwater resources critical for food production. Here, we leverage a unique multi-decadal dataset of well-level groundwater withdrawals for crop irrigation over the Kansas High Plains Aquifer to determine the interactions between groundwater depletion and growing farms. Holding key technological, management, and environmental variables fixed, we show that doubling a farm's irrigated cropland decreases groundwater extractions by 2%–5% depending on the initial farm size. However, a corresponding shift by larger farms to different irrigation technologies offsets this reduction in groundwater use, leading to a slight increase in overall groundwater use. We find groundwater depletion increases the likelihood farmland is sold to a larger farm, amplifying the cycle of groundwater depletion and the consolidation of farmland.